The effectiveness of a training program based on emotional intelligence skills to reduce the level of depression in a sample of blood pressure patients - A field study in the state of Laghouat - - kouidri , Ali; Laiche , Amel (Social Empowerment Journal, 2021)
The study aims to measure the effect of a training program based on emotional intelligence skills to reduce the level of depression in a sample of blood pressure patients in the state of Laghouat. The study sample was divided into two groups randomly. An experimental group: It consists of (10) patients to whom a training program prepared by the researchers is applied, and a group Control: It consists of (10) patients for whom the training program was not applied, and the researchers used the emotional intelligence scale, the depression scale, and the training session evaluation form, and the results of the study reached: - There are differences between the mean scores of the experimental and control groups in the post-measurement after applying the program to Emotional intelligence scale for the benefit of the experimental group, - There are differences between the mean scores of the experimental and control groups in the post-measurement after applying the program to the depression scale in favor of the control group, and there are no differences between the mean scores of the experimental group in the follow-up measurement in both the emotional intelligence scale and depression.